Monitoring lava dome extrusion of Merapi Volcano during 2018-2019, using low-cost UAV application - Putra, Raditya; Harijoko, Agung; Santoso, Agus Budi (2022)
Merapi volcano has a well-known eruption type, namely Merapi type, in which an extruded lava dome collapses and is accompanied by pyroclastic density current (PDC). This type of eruption makes morphological monitoring of the lava dome crucial in the hazard mitigation process. After the VEI 4 eruption in 2010, a new lava dome of Merapi appeared on top of the 2010 lava dome in August 2018 and continuously grew. In November 2019, the lava dome started to collapse outward the crater area. We reported the lava dome morphological monitoring using a UAV (Unmanned Aerial Vehicle) photogrammetry conducted from August 2018 to February 2019. This UAV monitoring provides processed aerial photo data in Digital Terrain Model (DTM) and orthophoto with low operating costs and short data acquisition time. The lava domes erupted from the same eruptive canter within this period and grew evenly in all directions. The 2018-2019 Merapi lava dome has basal ratio of 0.183 to 0.290 with height of 11 to 41 m, respectively. Volume changed from 33,623 m3 in August 2018 to 658,075 m3 in February 2019, suggesting growth rate at ∼3,500 m3/day. The lava base filled the crater base area (0.21 km2) and started to collapse outward in November 2019. © Published under licence by IOP Publishing Ltd.